The Effect of Sea Level Fluctuations on the Caspian Sea Coastline Changes - Soheil Ataei; Mehdi Adjami; Mir Ahmad Lashteh Neshaei; Seyed Hossein Ya'asubi (نشریه مهندسی دریا, 2017)
The Caspian Sea level changes were very high in various periods of time; alternatively decreasing and increasing. Since the Caspian Sea level changes generally are remarkable in the short period of time, shoreline forward and retreat will be large due to the fluctuation of sea level; so, the prediction of shoreline changes is very important in the Caspian Sea. Bruun has presented his theory under the title of Bruun rule for shoreline change prediction; this rule is related to sea level rise, closure depth, distance from the coastline to closure depth and the maximum vertical run-up excursion above the point of bore collapse parameters. Also, Rosati et al. applied landward transport to the Bruun rule for improvement of its prediction that achieved the most favorable results.